Impaired anticipatory postural adjustments due to experimental infrapatellar fat pad pain. (23rd February 2015) - Shiozawa, S.; Hirata, R.P.; Jeppesen, J.B.; Graven‐Nielsen, T.
Abstract Background Anticipatory postural adjustments (APAs) are motor responses generated to stabilize balance prior to voluntary movement. This study investigated how infrapatellar fat pad pain induces reorganization of APAs during reaction time tasks. It has been hypothesized that knee pain may cause insufficient APAs, thereby impairing the balance. Methods While standing, 12 healthy men performed two reaction time tasks (shoulder flexion of the dominant side and bilateral heel lift, respectively) before, during and after experimental infrapatellar fat pad pain induced in the dominant side by injections of hypertonic saline. Isotonic saline was injected as control. The reaction time task performance was assessed by peak angle and peak angular velocity. Timing and intensity of the postural muscle activity were recorded by surface electromyography. Results The reaction time task performance was not significantly affected by experimental pain. The onset of muscle activity in vastus medialis, vastus lateralis and tibialis anterior muscles on the dominant side during the bilateral heel lift task was significantly delayed during pain, and their muscle activity was reduced when compared with non‐painful sessions (p < 0.05). The contralateral vasti muscles demonstrated early onset during pain compared with the non‐painful session of the same task (p ≤ 0.05). Conclusions This study demonstrates that knee pain reorganizes the APAs which may destabilize the balance control. The knee pain‐related reorganization of postural muscle activity during APA may be a part of the central modulation to maintain posture and protect the painful limb while preserving the reaction task movement performance.